Evaluation of risdiplam efficacy in 5q spinal muscular atrophy: a systematic comparison of electrophysiologic with clinical outcome measures - Keßler, Tobias; Sam, Georges; Wick, Wolfgang; Weiler, Markus (European journal of neurology, 2023)
Background To assess compound muscle action potential (CMAP) amplitudes as electrophysiologic markers in relation to clinical outcome in adult patients with 5q-linked spinal muscular atrophy (SMA) before and during treatment with risdiplam. Methods In this monocentric longitudinal cohort study, CMAP of 18 adult patients with SMA type 2 or 3 were assessed at baseline (T0) and after 10 months (T10) of risdiplam treatment. CMAP amplitudes of the median, ulnar, peroneal, and tibial nerves were compared with established clinical outcome scores, and with the course of disease before start of treatment. Results During a pharmacotherapy-naive pre-treatment period of 328 ± 46 days, Revised Upper Limb Module (RULM) score and peroneal nerve CMAP amplitudes decreased, while CMAP of tibial and upper limb nerves remained unchanged. CMAP amplitudes positively correlated with clinical scores (Hammersmith Functional Motor Scale-Expanded [HFMSE], RULM) at T0. During risdiplam treatment, HFMSE and Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) scores increased, paralleled by marked increase of CMAP amplitudes in both median nerves (T10-T0; right: Δ = 1.4 ± 1.4 mV, p = 0.0003; left: Δ = 1.3 ± 1.4 mV, p = 0.0007), but not in ulnar, peroneal, or tibial nerves. A robust increase of median nerve CMAP amplitudes correlated well with an increase in the HFMSE score (T10-T0). Median nerve CMAP amplitudes at T0 were associated with subsequent risdiplam-related improvement of HFMSE and CHOP INTEND scores at T10. Conclusions Median nerve CMAP amplitudes increase with risdiplam treatment in adult SMA patients, and should be further evaluated as potential easy-to-use electrophysiologic markers in assessing and monitoring clinical response to therapy.